Retracted: Synthesis, Characterization, and Biological–Pharmacological Evaluation of New Phosphazenes Bearing Dioxybiphenyl and Schiff Base Groups (Arch. Pharm. Chem. Life Sci. (2012), 345, 6, (476–485), 10.1002/ardp.201100412) - Cil, Erol; Tanyildizi, Mehmet Ali; Ozen, Furkan; Boybay, Mustafa; Arslan, Mustafa; Gorgulu, Ahmet Orhan (John Wiley and Sons Inc, 2013)
The following article from the Archiv der Pharmazie,“Synthesis, Characterization, and Biological–Pharmacological Evaluation of New Phosphazenes Bearing Dioxybiphenyl and Schiff Base Groups” by Erol Cil, Mehmet Ali Tanyildizi, Furkan Ozen, Mustafa Boybay, Mustafa Arslan and Ahmet Orhan Gorgulu, published online on 13 March 2012 in Wiley Online Library (wileyonlinelibrary.com), has been retracted by agreement between the authors, the journal Editor-in-Chief Prof. Holger Stark and Wiley-VCH Verlag GmbH & Co. KGaA Weinheim. The retraction has been agreed due to errors in the biological-pharmacological results data and in the discussion and conclusions based on these data. © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: erratum; human